LANGUAGE LEARNING STRATEGIES USED BY SUCCESSFUL STUDENTS OF THE ENGLISH EDUCATION STUDY PROGRAM AT UNIVERSITY OF BENGKULU - Purnama Yulian Sari; Dedi Sofyan; Gita Mutiara Hati (Journal of English Education and Teaching, 2018)
This research is aimed at finding the language learning strategy used by successful students that is categorized into six kinds of strategies; memory, cognitive, metacognitive, affective, compensation, and social strategy suggested by Oxford (1990). The population of the research are students of English study program University Bengkulu year 2014 and 2015 that have GPA 3.51 to 4.00. Methodology of this research is descriptive quantitative. Data were collected by using questionnaires as the instruments. The questionnaires consist of 50 items based on Oxford’s Strategy Inventory for Language Learning (SILL) version 7.0 about language learning strategy. The data were processed by using Microsoft Excel 2013 to find the most dominant strategy used by the students. The results showed that the successful students use more than one language learning strategy or mixed strategy, including memory, cognitive, metacognitive, affective, compensation, and social strategy. The dominant strategy used by successful students was metacognitive with mean score 3.94 followed by compensation (3.81), cognitive (3.59), social (3.43), memory (3.31), and affective strategy (3.30). Metacognitive strategies have positive and significant influence toward academic achievement on successful students in learning a language. Metacognitive strategies can help the students to develop good thinking management ability. It also create good academic achievement. In the other hand, the choice of lowest strategy seems to be affected by technology advances, curriculum, feelings, mood, and attitude of the students which is unpredictable.